U-shaped relationship in international entrepreneurship: entrepreneurial orientation and innovation as drivers of internationalisation of firms - Wach, Krzysztof; Maciejewski, Marek; Głodowska, Agnieszka (Technological and Economic Development of Economy, 2022)
This article aims to identify and verify the relationship between entrepreneurial orientation and innovation of internationalised firms from Poland as a former emerging market. The article assesses this relationship in terms of the internationalisation scope. We adopted a quantitative research design and conducted a CATI survey on a sample of 355 firms operating in Poland. To verify the various assumed relationships, we used statistical instruments, including descriptive statistics and simple linear regression. Entrepreneurial orientation influences the innovations of internationalized firms. The impact depends on the scope of internationalization and is U-shaped. The impact of entrepreneurial orientation on innovation is greater for firms with large and small scope of internationalization. A relatively lower impact of entrepreneurial orientation on innovation is visible for firms with a moderate scope of internationalization. The study is an original contribution to the literature. Firstly, we perceive entrepreneurial orientation as a variable that can determine corporate innovation. Secondly, most of the empirical research to date focuses on highly developed markets. Firms that go beyond the borders of emerging markets see internationalization as a way of gaining experience, learning, and an opportunity to improve their innovative capacity. Thirdly, the study contributes to the development of theories combining entrepreneurial orientation with innovation by applying a new concept of a U-shaped curve.First ublished online 20 May 2022